Robotic pancreatoduodenectomy provides better short-term outcomes as compared to its laparoscopic counterpart: a meta-analysis - Liu, Faying; Zou, Yang; Chen, Qing; Chen, Tao; Xiao, He; Xie, Tingbing; Zheng, Lihe; Ruan, Qi; Liu, Wang (Frontiers in Oncology, 2025)
ObjectiveMinimally invasive pancreaticoduodenectomy is becoming more and more popular among surgeons, but whether robotic pancreatoduodenectomy (RPD) is superior to laparoscopic surgery remains controversial. The study aims to assess the available literature and compare the perioperative outcomes of RPD and laparoscopic pancreatoduodenectomy (LPD).MethodsA systematic literature search was performed in the PubMed, Cochrane Library, Embase, Web of Science databases (October 2024). Risk ratios (RRs) and mean differences (MDs) with 95% confidence intervals (CIs) were calculated.ResultsThe 29 studies that met inclusion criteria included 15137 PDs, out of which 8935 were LPD and 6202 were RPD. Compared with LPD, RPD has lower overall complications (RR, 0.87), conversion rates (RR, 0.47) and blood transfusion rates (RR, 0.56), shorter length of stay (MD, -0.80 days), and higher number of harvested lymph nodes (MD, 1.77). There were no significant differences observed in 90-day mortality (RR, 0.92), major complications (RR, 1.00), operative time (MD, 3.93 mins), blood loss (MD, -22.50 mL), reoperation (RR, 0.96), bile leak (RR, 0.87), postoperative pancreatic fistula (RR, 1.00), delayed gastric emptying (RR, 1.19), and R0 resection (RR, 0.99) between the groups.ConclusionsRobotic-assisted surgery for PD is safe and feasible. Compared to LPD, it offers better short-term outcomes.